Relationship between risk of osteoporotic fractures and muscle strength in community dwelling adults/ Chua Siew Kuan, Azianah Mohamad Ibrahim & Azni Ahmad - Chua, Siew Kuan; Mohamad Ibrahim, Azianah; Ahmad, Azni (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Identified osteoporotic fracture risk is crucial as increase prevalence of aging population with low bone density. Frailty and falls commonly in adults with osteopenia than osteoporosis. This study aimed to examine the relationship between grip strength, biceps and quadriceps muscle strength, and 10-year probability of risk of osteoporotic fracture (FRAX). A cross-sectional study conducted among hundred community dwelling adults aged ≥40 years. Clinical risk factors screened by health screening questionnaire included demographic data, FRAX risk factors and other healthrelated information. Dynamometer used to measure grip strength, spring scale matric for bicep and quadriceps strength, Singapore model of FRAX Tool utilized to determine risk of hip and non-hip fracture. The mean age of participants was 58±8.7 years, almost all participants were at low risk of non-hip and hip fracture. The 10-year risk of hip and non-hip fracture had negative significant (all p < 0.01) correlation with hand grip strength (r = -0.22), bicep strength (r = -0.3- -0.38) and quadriceps strength (r = -0.2 & -0.34). Grip strength, biceps and quadriceps muscle strength may along assess with risk factors in FRAX Tool, as a health screening in identify who are at high risk of osteoporotic fracture in community dwelling adults.